Începuturile învățământului artistic la Târgu Mureș. Institutul de Teatru „Szentgyörgyi Istvan“ - Pășcan, Sabin-Gavril (Theatrical Research, 2023)
The Beginnings of Artistic Education in Târgu Mureș. The “Szentgyorgi Istvan” Theatre Institute Târgu Mureș is recognized today as one of the most valuable theatre centres in Romania, and the audience from Târgu Mureș is demanding but also generous. The appearance of the Târgu Mureș theatre somewhat coincided with the appearance of the Theatre Institute after the Second World War. If at the beginning the plays were performed only in Hungarian, after 1962 the theatre became intercultural when the Romanian section of the State Theatre in Târgu Mureș was established. In the 1960s and 1970s, theatrical artistic education occupied a special place in the education system. The specialized department of the Institute, the Art of the Actor, which had the role of creating the artistic-professional education of the students, was made up entirely of “specialists from outside the school” – that is, of the qualified actors of the State Theatre of Târgu Mureș. In 1976, after 22 years in which Transylvania was bereft of the Romanian theatre school, the reorganization of the Institute took place by establishing the Romanian section, specializing in acting, in Târgu Mureș. The Theater Institute in Târgu Mureș is today a renowned higher education institution in the theatrical field in Romania and offers students the opportunity to develop as professionals in a creative and stimulating environment.